Evolución de la diabetes mellitus a enfermedad renal crónica - Trejo Tapia, Felipe de Jesús (Universidad Michoacana de San Nicolás de Hidalgo, 2010)
Chronic kidney disease have been acquired epidemic proportions, the major etiology is type 2 diabetes mellitus (DM) and high blood pressure. Objective: To evaluate the time of evolution from the initial diagnose of DM to chronic renal failure (CRF) and the renal replacement therapy (RRT), and its association with glycemic control. Design: A retrospective, observational and descriptive study was conducted, in primary care and hospitalization services. Methods: The files of patients with CRF were reviwed, inclusion criteria were: patients in any of the dialysis program secondary to DM, exclusion criteria: CRF secondary to other diseases different to DM. Data are expressed as mean ± SEM and are presented as tables and figures. Results: 538 files of patients with CRF were reviwed. 148 were included. The dyalisis program of those was: 95 (64%) peritoneal dialysis, 43 (29%) hemodialysis, 10 (7%) renal replacement. The time of evolution to renal failure secondary to DM was 17 ± 1.6 years (1-33 years). The diagnose was established with the result of a creatinine plasma clearance (Ccr) of 13.8 ± 4.2 ml/min/1.73m2 (2.37-55.9 ml/min/1.73m2); the RRT was started 1.2 ± 0.27 years after the diagnose IRC (0 -- 8 years). Ony 15% of patients were referred to the nephrology service in early stage. Conclusions: Our data show that patients with DM develop CRF in 17.01 ± 1.64 years. 85% of patients were referred to the nephrology from the primary care unit in an early stage, despite Ccr.

La enfermedad renal crónica (ERC) ha adquirido proporciones de una epidemia. Las principales causas diabetes mellitus (DM) e hipertensión arterial (HTA). Objetivo: Evaluar el tiempo de evolución a enfermedad renal crónica en fase terminal (ERFT) en pacientes con DM y su asociación con el control glucémico. Diseño: Estudio retrospectivo, observacional y descriptivo en el primer y segundo nivel de atención. Métodos: Se revisaron expedientes de pacientes con ERFT, se incluyeron derechohabientes del IMSS que acuden al HGR1 a terapia renal de remplazo (TRR) con ERFT secundaria a DM, excluyendo a pacientes con ERFT secundaria a DM con otra comorbilidad asociada. Los datos se expresan en media ± ESM Resultados: De 538 expedientes de pacientes con ERFT, 148 cumplieron los criterios de selección, 95 (64%) en diálisis peritoneal, 43 (29%) en hemodiálisis, 10 (7%) con trasplante renal. El tiempo de evolución de daño renal por DM fue de 17.01±1.64 años (1-33 años). El diagnostico se realizó con depuración de creatinina (DCr) de 13.8 ± 4.2 ml/min./1.73m2 (2.37-55.9 ml/min/1.73m2) y la TRR se inicio 1.2±0.27 años después del diagnóstico de ERC (0-8 años). El 15% fueron derivados tempranamente al servicio de Nefrología. Conclusiones: Nuestros datos reflejan que los pacientes con DM desarrolla ERFT en 17.01 ± 1.64 años. El 85% de los pacientes no fueron referidos de MF al servicio de Nefrología tempranamente, lo cual permitiría al paciente nefrópata una mejor calidad de vida.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4142; info:eu-repo/classification/cti/3; FCMB-E-2010-0042; Terapia renal de remplazo; Nefropatía diabética; Índice de excreción de albumina urinaria